Decay Corrections in Isotopic Ratio Estimation for Short-Lived CTBT-Relevant Radionuclides Based on Activity Concentration Profiles During Sampling - Boxue Liu; Joshua Kunkle; Robin Schoemaker; Christos Saragiotis; Yuichi Kijima; Martin Kalinowski (Pure and Applied Geophysics, 2025)
Isotopic activity ratios of the relevant radionuclides detected at radionuclide stations within the International Monitoring System (IMS) for the Comprehensive Nuclear-Test-Ban Treaty (CTBT), are crucial for characterizing release events under assumed scenarios. This analysis involves considering radioactive gases initially released from an underground nuclear event, resulting in radionuclide concentrations in a plume of air passing over an IMS station that are subsequently sampled by that station. Modeling this process requires considering the post-detonation radionuclide evolution of an assumed underground nuclear explosion, simulating atmospheric transport, and finally, collecting and measuring samples. Activities collected in the samples are determined through spectrum analysis of sample measurements, and the activity concentrations are then estimated by assuming a constant concentration during sampling. While this assumption holds true for radionuclides with relatively longer half-lives, exceeding 7 times the sampling duration, challenges arise for isotopes with short half-lives, such as 135 Xe with half-life of 9.14 h compared to the 12-h collection duration for some noble gas systems. Therefore, this study investigates decay correction during sampling using two approaches: 1) Interval constant concentration: the collection duration is divided into multiple intervals, with a constant concentration assumed in each interval; 2) Decaying concentration: the activity collected in the sample is derived based on an analytical solution to the ordinary differential equations governing the activity decay and ingrowth. The impact of these approaches on isotopic activity ratios is demonstrated in three cases with short half-lives: 140 Ba/ 140 La, and 133m Xe/ 133 Xe, and 135 Xe/ 133 Xe. The decay correction on the ratio 135 Xe/ 133 Xe might be approximately 2 for 24-h sampling, and 1.2 for the shortest collection duration of 6 h. For the pair of 133m Xe to 133 Xe, the ingrowth correction might be negligible compared to the relatively large value of the ratio 133 Xe/ 133m Xe, which exceeds 10 in a few days after the detonation. For the ratio 140 La/ 140 Ba, the contribution from the ingrowth of parent-daughter decay is approximately 0.35 for a collection duration of 24 h.

Investigation of Radioxenon Probability Density Functions at IMS Radionuclide Stations Using a Monte Carlo Method for Background Estimation - Yuichi Kijima; Robin Schoemaker; Anne Tipka; Boxue Liu; Joshua Kunkle; Jolanta Kuśmierczyk-Michulec; Martin Kalinowski; Mark Prior; Megan Slinkard (Pure and Applied Geophysics, 2025)
The International Monitoring System, the primary means of verification of the Comprehensive Nuclear-Test-Ban Treaty, monitors the planet for any sign of a nuclear explosion. Regarding the International Monitoring System radionuclide stations, it is known that radioxenon released from nuclear facilities such as medical isotope production facilities and nuclear power plants influences the stations. For the purposes of monitoring nuclear explosions, it is important to better understand the radioxenon background based on these nuclear facilities. The probability density functions of background activity concentration at IMS radionuclide stations are estimated using a Monte Carlo method based on emissions from known nuclear facilities and source receptor sensitivity data. This paper describes two case studies of radioxenon detections at radionuclide stations applying the developed approach. This method could be one of several prospective approaches to predict the activity concentrations of isotopes of radioxenon at radionuclide stations in Comprehensive Nuclear Test-Ban Treaty Organization’s (CTBTO’s) prototype xenon background estimation tool software. It can also be used in characterization of CTBT-relevant nuclear events for expert technical analysis. Plain Language Summary Civil nuclear power stations and medical isotope production facilities release radioisotopes of xenon during their normal operations. These emissions would make it harder to detect xenon produced from any nuclear weapon test that might occur. A method is described that starts with information about civil releases and produces a statistical description of the concentrations of isotopes measured at stations designed to detect nuclear tests. This information makes it possible to enhance nuclear explosion detection performance.

Correction: Investigation of Radioxenon Probability Density Functions at IMS Radionuclide Stations Using a Monte Carlo Method for Background Estimation - Yuichi Kijima; Robin Schoemaker; Anne Tipka; Boxue Liu; Joshua Kunkle; Jolanta Kuśmierczyk-Michulec; Martin Kalinowski; Mark Prior; Megan Slinkard (Pure and Applied Geophysics, 2025)

Correction: Characterization of CTBT-Relevant Radioxenon Detections at IMS Stations Using Isotopic Activity Ratio Analysis - Boxue Liu; Martin Kalinowski; Yunwei Sun; Charles R. Carrigan; Christos Saragiotis; Jun Wang; Martin Ertl; Yuichi Kijima; Robin Schoemaker; Jolanta Kuśmierczyk-Michulec; Anne Tipka; Tarabay Antoun (Pure and Applied Geophysics, 2024)

Investigation on atmospheric radioactivity sample association using consistency with isotopic ratio decay over time at IMS radionuclide stations - Yuichi Kijima; Robin Schoemaker; Boxue Liu; Joshua Kunkle; Anne Tipka; Jolanta Kuśmierczyk-Michulec; Martin Kalinowski (Journal of Environmental Radioactivity, 2023)

Characterization of CTBT-Relevant Radioxenon Detections at IMS Stations Using Isotopic Activity Ratio Analysis - Boxue Liu; Martin Kalinowski; Yunwei Sun; Charles R. Carrigan; Christos Saragiotis; Jun Wang; Martin Ertl; Yuichi Kijima; Robin Schoemaker; Jolanta Kuśmierczyk-Michulec; Anne Tipka; Tarabay Antoun (Pure and Applied Geophysics, 2023)
Radioxenon isotopes measured at radionuclide stations of the Comprehensive Nuclear-Test-Ban Treaty’s (CTBT) International Monitoring System (IMS) may indicate releases from underground nuclear explosions (UNEs) but are often caused by emissions from nuclear facilities. Characterization of CTBT-relevant nuclear events may use the evolution of isotopic activity ratios over time, which goes from the release of an assumed UNE, through atmospheric transport, to sample collections and measurements. A mathematical approach is presented to discuss the characterization of the spatial and temporal relationships between a nuclear explosion and radioxenon measurements. On the one hand, activity concentrations at an IMS station are estimated by using the assumed release scenario regarding a UNE and atmospheric transport modelling. On the other hand, the activities collected in the samples are determined by spectral analysis first and the activity concentrations in the air passing over the IMS station are estimated under an assumption of constant concentration during sampling. The isotopic ratios of activities released from the UNE are related to the isotopic ratios of activity concentrations in the plume of air crossing the IMS station, resulting in a function of the isotopic activity ratio over the time from detonation to sample measurement. The latter is used for discrimination of a nuclear test and estimation of the time of detonation, such as a four radioxenon plot of the activity ratio relationship of 135 Xe/ 133 Xe versus 133m Xe/ 131m Xe.